Ownership patterns and enterprise groups in German structural business statistics - John P. Weche Gelübcke (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2011)
First official data on enterprise groups and foreign majority ownership for Germany became available recently. The new firm-level information is linked to core German structural business statistics, the URS, and therefore offers a wide variety of new research possibilities in fields that often fall victim to polarizing public and academic debate of high relevance to policy decisions. German official statistics generally offer a high quality level, but, since private vendor data integration and processing of data on capital links remain in development, new features of representativeness must prove themselves in the future.
Keywords: 330; Statistik der Unternehmen und Arbeitsstätten; Wirtschaftsstruktur; Eigentümerstruktur; Deutschland